Humic Acid Removal from Aqueous Environments by Electrocoagulation Process Using Iron Electrodes. Issue 4 (2012) - Bazrafshan, Edris; Biglari, Hamed; Mahvi, Amir Hossein
Abstract : At present study the performance of electrocoagulation process using iron electrodes sacrificial anode has been investigated for removal of HA from artificial aqueous solution. The experiments were performed in a bipolar batch reactor with four iron electrode connected in parallel. Several working parameters, such as initial pH (3, 5, 7, and 9), electrical conductivity (50 V) and reaction time were studied in an attempt to achieve the highest removal capacity. Solutions of HA with concentration equal 20 mg L -1 were prepared. To follow the progress of the treatment, samples of 10 ml were taken at 15, 30, 45, 60, and 75 min interval. Finally HA concentration was measured by UV absorbance at 254 nm (UV254 ) and TOC concentration was measured by TOC Analyser. The maximum efficiency of HA removal which was obtained in voltage of 50 V, reaction time of 75 min, initial concentration 20 mg L -1, conductivity 3000 µS/Cm and pH 5, is equal to 92.69%. But for natural water samples at the same optimum condition removal efficiency was low (68.8 %). It can be concluded that the electrocoagulation process has the potential to be utilized for cost-effective removal of HA from aqueous environments.